Some New Oscillation Criteria for Certain Class of Quasilinear Elliptic Equations - Dhanalakshmi , C.; Chatzarakis, G. E.; Sadhasivam, V.; Priyadharshini, S. (Communications in Mathematics and Applications, 2025)
The main goals of this paper is to investigate a new oscillation for a certain class of quasilinear elliptic equations by using Riccati technique. Our main results are demonstrated with an example.